Retraction Note: MicroRNA-1468 promotes tumor progression by activating PPAR-γ-mediated AKT signaling in human hepatocellular carcinoma - Zhikui Liu; Yufeng Wang; Changwei Dou; Liankang Sun; Qing Li; Liang Wang; Qiuran Xu; Wei Yang; Qingguang Liu; Kangsheng Tu (Journal of Experimental & Clinical Cancer Research, 2022)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13046-018-0717-3